Implementation of Brain Exercises on Power Changes Remember the Elderly at Iryou Houjin Fukujukai Nishihara Keiaien Japan - Agustina, Dewi Yulia; Setianingsih, Setianingsih (Global Health Science Group, 2024)
The process from adulthood to old age causes cognitive impairment to the memory abilities of the elderly. As an effort to overcome the decline in cognitive function in the elderly, nursing staff can do this by carrying out non-pharmacological therapy, namely brain exercises. Brain exercises are a number of simple movements that can balance each part of the brain, can draw out the level of brain concentration and provide some solutions for blocked parts of the brain so they can function optimally. Improving memory function can prevent a complete decline in the intellectual, cognitive and emotional functions of the elderly. This research aims to find out whether there are brain exercises on changes in memory in the elderly. The method used is a case study which involves several stages of the nursing care process starting from assessment, diagnosis, intervention, implementation and nursing evaluation with a focus on nursing diagnoses, namely memory disorders. After giving brain exercise training for 3 x 15 minutes, it was proven to have an effect on changes in memory. The implementation of brain exercises has been proven to be effective in increasing changes in memory. Brain exercises can improve language skills and memory, including the right brain and left brain, to the cerebrum, the brain flows to the cerebrum and affects cognitive function.